Applicability of the Hebrew Bible to Post-traumatic Stress Disorder and Post-traumatic Growth - Li, Xi (Journal of religion and health, 2024)
Since the new millennium, biblical scholars have begun to reread certain writings in the Hebrew Bible through the concepts of post-traumatic stress disorder and post-traumatic growth. Some scholars believe such a reading is legitimate, whereas others think it problematic, and still, others hold a midway perspective. This article argues for the midway, the position that accepts the applicability of the Hebrew Bible to today’s psychological concepts but calls for caution. Because ancient Israelites reacted to traumatic events and distinguished the human mind from the body like modern people, it is reasonable to approach their thoughts and emotions in the Hebrew Bible through today’s psychological concepts. However, the cultural differences between today’s society and ancient Israelites in understanding and reacting to traumatic events should be considered.